Respuesta :

Answer:

Step-by-step explanation:

just think of the parts of an equation as just regual number

a = 5      b = 8      a × b  =  5 × 8     =  40

now f(x) =  x² + 3x     and g(x) = 2x²      

f(x) × g(x)      =     (x² + 3x) × (2x²)

                    =     (x² × 2x²) + (3x × 2x²)

                    =     2x^4  + 6x^3

f(x) × g(x)  = 2x^4  + 6x^3    < ------------------ FINAL ANSWER

let x =2   in (x² + 3x) × (2x²)  

        (2² + 3×2) × (2×2²) = (4+6) (8) = (10×8) = 80

f(x) × g(x)  = 2x^4  + 6x^3

      =  2×16 + 6×8

      = 32 + 48

      = 80      it checks as correct